Characteristics of sub-bottom profile acquired in Shatt Al-Arab River, Basrah-Iraq - Alaamer, H.A. (Mesopotamian Journal of Marine Sciences, 2022)
A single sub bottom profile, nearly 1.0 km long, was acquired in Shatt Al-Arab River, at the river’s portion next to the downtown of Basrah city, 2010. The profile characterized by predominant ripple-marked features. Beneath the bottom, signal penetration was relatively low attributed to the existence of thick layer identified in the sub-bottom and interpreted as the main load bearing layer in the area. Riverbed multiple showed a strong presence and occupied the profile’s bottom. Interpretation beyond the riverbed multiple was not possible. Water bottom was flat, except for a buried object of undetermined type lying within the sediments of the bottom.